Prevalence of presenile dementia in a tertiary outpatient clinic - Satomi Fujihara; Sonia M.D. Brucki; Maria Sheila G. Rocha; Alzira A. Carvalho; Ana C. Piccolo (Arquivos de Neuro-Psiquiatria, 2004)
There are very few reports about prevalence of presenile dementia in Brazil. We reviewed files of patients evaluated with early onset of cognitive impairment in our institution. Among 141 patients (61% males) there was no difference between gender by age at onset or at first evaluation. We have observed an increasing number of patients after 50 years. The most frequent causes were: vascular dementia (36.9%), Alzheimer's disease (20.3%) and traumatic brain injury (9.2%). There was difference among dementia type by age of onset and first evaluation, educational level and length of dementia. These results may be compared with those from other neurologic services in order to replicate or confirm these results.